Fluoroquinolone prophylaxis in haematological cancer patients with neutropenia: ECIL critical appraisal of previous guidelines. Issue 1 (January 2018) - Mikulska, Malgorzata; Averbuch, Diana; Tissot, Frederic; Cordonnier, Catherine; Akova, Murat; Calandra, Thierry; Ceppi, Marcello; Bruzzi, Paolo; Viscoli, Claudio; ,
Highlights: The role of fluoroquinolone prophylaxis (FQ-P) during neutropenia in the times of increasing antibiotic resistance has to be established. In studies published after 2005, FQ-P had no effect on mortality, but it reduced the rate of bloodstream infections and episodes of fever. No effect of background rate of resistance of E. coli to FQs was shown for the setting with FQ resistance rate below 27% Use of FQ prophylaxis should depend on local epidemiology and policy on antimicrobial use Summary: Objectives: Fluoroquinolone (FQ) prophylaxis was recommended in 2005 by European Conference on Infections in Leukemia (ECIL) for patients with prolonged neutropenia. In consideration of a worldwide increase in antibiotic resistance, the issue of FQ prophylaxis during neutropenia was re-evaluated. Methods: Literature review of randomised controlled trials (RCT) and observational studies published in years 2006–2014 was performed. Their results were analysed in meta-analysis. Meta-regression model was applied to evaluate whether the rates of FQ resistance in community and hospital settings influenced the efficacy of FQ prophylaxis. The impact of FQ prophylaxis on colonisation and infection with resistant bacteria was reviewed. Results: Two RCTs and 12 observational studies were identified. FQ prophylaxis did not have effect on mortality (pooled OR 1.01, 95%CI 0.73–1.41), but was associated with lower rate of bloodstream infections (BSI) (pooled OR 0.57, 95%CI 0.43–0.74) and episodes of fever during neutropenia (pooled OR 0.32, 95%CI 0.20–0.50). No effect of the background rate of FQ resistance on the efficacy of FQ prophylaxis was observed. In few studies, FQ prophylaxis resulted in an increased colonisation or infection with FQ- or multi-drug resistant strains. Conclusions: The possible benefits of FQ prophylaxis on BSI rate, but not on overall mortality, should be weighed against its impact in terms of toxicity and changes in local ecology in single centres.